2016
DOI: 10.1183/13993003.01899-2015
|View full text |Cite
|
Sign up to set email alerts
|

Clinical phenotypes in adult patients with bronchiectasis

Abstract: Bronchiectasis is a heterogeneous disease. This study aimed at identifying discrete groups of patients with different clinical and biological characteristics and long-term outcomes.This was a secondary analysis of five European databases of prospectively enrolled adult outpatients with bronchiectasis. Principal component and cluster analyses were performed using demographics, comorbidities, and clinical, radiological, functional and microbiological variables collected during the stable state. Exacerbations, ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
193
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 242 publications
(211 citation statements)
references
References 27 publications
11
193
0
7
Order By: Relevance
“…We observed strong relationships between NE activity and bacterial load. NE activity was also highest in patients with P. aeruginosa infection, and this was consistent with previous studies in bronchiectasis that showed that bacteria, and P. aeruginosa in particular, were the key drivers of airway neutrophilic inflammation (22), and that that P. aeruginosa infection represented a distinct clinical phenotype associated with earlier mortality, more frequent exacerbations, and worse quality of life (14,22,29,30).…”
Section: Discussionsupporting
confidence: 78%
“…We observed strong relationships between NE activity and bacterial load. NE activity was also highest in patients with P. aeruginosa infection, and this was consistent with previous studies in bronchiectasis that showed that bacteria, and P. aeruginosa in particular, were the key drivers of airway neutrophilic inflammation (22), and that that P. aeruginosa infection represented a distinct clinical phenotype associated with earlier mortality, more frequent exacerbations, and worse quality of life (14,22,29,30).…”
Section: Discussionsupporting
confidence: 78%
“…On one hand, we can speculate that frequent exacerbators are also those with either an intermittent infection with P. aeruginosa or chronic infections with other bacteria, as recently reported [8], and that microbiology is just one of several bronchiectasis features responsible for bad outcomes [7]. On the other hand, hospitalisations for LRTI in bronchiectasis patients might be also due to factors not strictly related to bronchiectasis and infection, such as the presence of decompensated comorbidities or failure of oral antibiotic therapy [9].…”
Section: To the Editormentioning
confidence: 74%
“…P. aeruginosa colonisation defines a specific clinical phenotype of bronchiectasis, and is associated with a three-fold increase risk of death, a nearly seven-fold increase risk of hospital admissions, worse quality of life and more frequent exacerbations [27][28][29]. Evidence from CF suggests that attempts at eradication therapy targeting Pseudomonas can have success in converting patients to culture-negative status [30].…”
Section: Important Research Priorities Identified By Expertsmentioning
confidence: 99%